Upaya Meningkatkan Kemandirian Belajar Siswa Melalui Lesson Study Kelas V SD Negeri 0605 Simanuldang - Alwi Hamdani Hasibuan; Rahma Sari Harahap; Mancar; Nurhayati Siregar (Dirosah Islamiyah: Jurnal Studi Islam, 2026)
Based on the research results, it can be concluded that: (1) The learning independence of class V students of SD Negeri 0605 Simanuldang pre-cycle is still low, namely 6 students or 20.00% learning independence is